Enhancing Users’ Perceived Significance of Academic Library with MOOC Services - Lazarus, Flora Charles; Suryasen, Rajneesh (Evidence Based Library and Information Practice, 2022)
Objective – Academic libraries have been impacted by the tremendous changes taking place in higher education due to the arrival of the internet and web-based technologies. Several articles have shown the decline in library usage and user need for electronic resources. The entry of MOOCs into higher education has repurposed the library’s roles and services. This research aims to explore the possible MOOC services of academic libraries and their effect on the user perception towards the significance of academic libraries.Methods – The academic library’s MOOC services are derived from the extensive literature review and subsequently a research model based on extant literature has been developed to evaluate user behaviour. The research model is evaluated using confirmatory factor analysis methods.Results – The academic library’s services for MOOCs have been categorized as, (a) user support services, (b) information services, and (c) infrastructure services. The study shows that each of these service categories have a positive impact on the library usage intention of the users. This in turn has a positive effect on the library’s perceived significance.Conclusion – The library services for MOOC users defined in this research and the findings are useful for librarians to develop new service strategies to stay relevant for the user.